A Rare Case of Acute Kidney Injury: McKittrick Wheelock Syndrome (Iranian Journal of Kidney Diseases, 2019)
McKittrick-Wheelock syndrome is a rare complication of rectosigmoid villous adenoma leading to secretory diarrhea, prerenal acute kidney injury and severe fluid and electrolyte imbalances. There are about 50 cases reported in literature. We represent a case of 71 year-old patient with persistant chronic diarrhea, prerenal azotemia, severe hypokalemia, and hyponatremia. Initially, the patient's kidney function and serum potassium values were normalized by conservative treatment, and villous adenoma was removed by surgery.